# 3x 2 12

﻿

## Solve 3x^212=0, Microsoft Math Solver

The difference of squares can be factored using the rule: a^ {2}b^ {2}=\left (ab\right)\left (a+b\right). x=2 x=2. To find equation solutions, solve x2=0 and x+2=0. 3x^ {2}=12. Add 12 to both sides. Anything plus zero gives itself. x^ {2}=\frac {12} {3} Divide both sides by 3. x^ {2}=4.

## Solve 3x^2+20x+12=0, Microsoft Math Solver

Steps Using Factoring By Grouping. 3 x ^ { 2 } + 20 x + 12 = 0. 3 x 2 + 2 0 x + 1 2 = 0. To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 3x^ {2}+ax+bx+12. To find a and b, set up a system to be solved.

## Solve Quadratic equations 3x^2+4x12=27 Tiger Algebra

2.1 Factoring 3x2+4x39. The first term is, 3x2 its coefficient is 3 . The middle term is, +4x its coefficient is 4 . The last term, "the constant", is 39. Step1 : Multiply the coefficient of the first term by the constant 3 39 = 117. Step2 : Find two factors of 117 whose sum equals the coefficient of

## Solve x^23x+2, Microsoft Math Solver

First, the expression needs to be rewritten as x 2 + a x + b x + 2. To find a and b, set up a system to be solved. a+b=3 ab=1\times 2=2. a + b = 3 a b = 1 × 2 = 2. Since ab is positive, a and b have the same sign. Since a+b is negative, a and b are both negative. The only such pair is the system solution.

## Graph y=3x12, Mathway

To find the xintercept (s), substitute in 0 0 for y y and solve for x x. 0 = 3 x 12 0 = 3 x 12. Solve the equation. Tap for more steps... Rewrite the equation as 3 x 12 = 0 3 x 12 = 0. 3 x 12 = 0 3 x 12 = 0. Add 12 12 to both sides of the equation. 3 x = 12 3 x = 12. Divide each term by 3 3 and simplify.

## Solve for x 2/3x=12, Mathway

Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with stepbystep explanations, just like a math tutor.

## 3x^2+4x12=0 solution

Solution for 3x^2+4x12=0 equation: Simplifying 3x 2 + 4x + 12 = 0 Reorder the terms: 12 + 4x + 3x 2 = 0 Solving 12 + 4x + 3x 2 = 0 Solving for variable ''x''. Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by ''3''. 4 + 1.x + x 2 = 0 Move the constant term to the right: Add ''4'' to each side of the equation. 4 + 1.x